Signal-in-space range error and positioning accuracy of BDS-3 - Weiping Liu; Bo Jiao; Jinming Hao; Zhiwei Lv; Jiantao Xie; Jing Liu (Scientific Reports, 2022)
Abstract Being the first mixed-constellation global navigation system, the global BeiDou navigation system (BDS-3) designs new signals, the service performance of which has attracted extensive attention. In the present study, the Signal-in-space range error (SISRE) computation method for different types of navigation satellites was presented. The differential code bias (DCB) correction method for BDS-3 new signals was deduced. Based on these, analysis and evaluation were done by adopting the actual measured data after the official launching of BDS-3. The results showed that BDS-3 performed better than the regional navigation satellite system (BDS-2) in terms of SISRE. Specifically, the SISRE of the BDS-3 medium earth orbit (MEO) satellites reached 0.52 m, slightly inferior compared to 0.4 m from Galileo, marginally better than 0.59 m from GPS, and significantly better than 2.33 m from GLONASS. The BDS-3 inclined geostationary orbit (IGSO) satellites achieved the SISRE of 0.90 m, on par with that (0.92 m) of the QZSS IGSO satellites. However, the average SISRE of BDS-3 geostationary earth orbit (GEO) satellites was 1.15 m, which was marginally inferior to that of the QZSS GEO satellite (0.91 m). In terms of positioning accuracy, the new signals B1C and B2a are considered together with the transition signals B1I and B3I. The overall three-dimensional single-frequency standard point positioning (SPP) accuracy of BDS-3 B1C, B2a, B1I, and B3I gained an accuracy level better than 5 m. Moreover, the B1I signal exhibited the best positioning accuracy in the Asian-Pacific region, while the B1C signal set forth the best positioning accuracy in the other regions. Owing to the advantage in signal frequency, the dual-frequency SPP accuracy of B1C + B2a surpassed that of the transitional signal of B1I + B3I. Since there are more visible satellites in Asia–Pacific, the positioning accuracy of BDS-3 was moderately superior to that of GPS. The precise point positioning (PPP) accuracy of BDS-3 B1C + B2a or B1I + B3I converged to the order of centimeters, marginally inferior to that of the GPS L1 + L2. However, these three combinations had a similar convergence time of approximately 30 min.